Animal effects on dissolved organic carbon bioavailability in an algal controlled ecosystem. (2nd December 2019) - Parr, Thomas B.; Vaughn, Caryn C.; Gido, Keith B.
Abstract: Animals exert both direct and indirect controls over elemental cycles, linking primary producer‐based (green) and decomposer‐based (brown) food webs through top‐down trophic interactions and bottom‐up element regeneration. Where animals are aggregated at high biomass, they create hotspots of elemental cycling. The relative importance of animal control on elemental cycling depends on animal biomass, species functional traits (i.e. feeding mode and stoichiometry), and their overlap. We evaluated how animal community complexity affects the mechanisms regulating energy flow to the brown food web. We conducted a mesocosm experiment where we varied the biomass and overlap of animals with different life history and stoichiometric traits (stream fish and mussels) and measured how this influenced the quantity and fraction of labile carbon available to microbes. We used linear models and structural equation modelling to evaluate direct (excretion) and indirect (herbivory, nutrient availability, and nutrient stoichiometry) effects of animals on bioavailable dissolved organic carbon (BDOC) concentration. In experimental stream mesocosms, we found support for both direct (DOC excretion) and indirect (grazing) animal influences on BDOC concentration. Although we found that snail, fish, and mussel biomass increased nutrient concentrations, neither nutrient concentration nor stoichiometry had a significant effect on BDOC concentration. This has been due to the high background nutrient concentration context of our stream mesocosm water. Snails, probably due to their high biomass and small body size, exerted a significant positive direct control on BDOC concentration. Fish and mussels exerted a significant negative indirect control on BDOC via their effects (grazing and bioturbation) on algal biomass. Our results imply that primary consumers with different feeding strategies provide a key mechanism regulating the flow of DOC into the brown food web through direct (excretion) and indirect (grazing) controls on primary producers. This highlights that animals can provide important controls on the production of bioavailable organic energy supporting microbes in aquatic ecosystems, but the importance of these controls depends on the nutrient context and the distribution of primary producer and animal biomasses.